Coronary plaque assessment by coronary computed tomography angiography - Indrihapsari, Pratiwi; Handari, Saskia Dyah (Heart Science Journal, 2025)
Coronary computed tomography angiography (CCTA) is a widely used non-invasive diagnostic technique in medical practice. It effectively detects, quantifies, and characterizes coronary artery plaques. With advancements in CCTA imaging, the quantity and quality of atherosclerotic plaques can now be accurately evaluated. This technique is commonly utilized to rule out the possibility of coronary artery disease and precisely assess how the condition impacts the coronary vessels. CCTA is a valuable diagnostic tool that can help identify high-risk plaque features and recommend appropriate treatment measures. By comparing morphological aspects of stable lesions with those of susceptible plaques, CCTA can help identify characteristics such as the napkin-ring sign, low CT attenuation, positive remodeling, significant plaque volume, and spotty calcification, which have been linked to an increased risk of acute coronary syndrome. To standardize the reporting of patients who undergo CCTA and guide probable following actions in patient care, the Coronary Artery Disease Reporting and Data System (CAD-RADS) was created. This system ensures that patient reports are consistent, accurate, and valuable for guiding appropriate treatment and care.